PRINCIPLES OF PATIENT CENTERED CARE (PCC) IN EMERGENCY NURSING CARE CARDIOVASCULAR ACTIVITY CASE - M Sobirin Mohtar; Faisal Amin; Esti Yuandari (CNJ: Caring Nursing Journal, 2021)
Emergency services are a sensitive area for nurses because of the urgent work environment that affects the quality of care for patients, especially in emergency cases. One of the effects is the lack of caring for emergency nurses who focus on patients (PCC) which can affect the quality of nursing services, especially in aspects of nursing care. This study aims to analyze the application of the principle of patient centered care (PCC) in emergency nursing care in cardiovascular emergency cases. This research uses the Literature Study method, in which literature searches are sourced from four databases (google scholar, DOAJ, PubMed, and Garuda Portal), using keywords that match the theme. From the 10 journals identified, it was found that there were various obstacles in the application of PCC principles in nursing care to patients with cardiovascular emergency from both the nurse and patient perspective. Nurses who apply PCC in every nursing care to patients sometimes experience various obstacles, namely services that are not accompanied by caring attitudes. Therefore, a solution is needed, such as training on the application of PCC to improve the quality of nursing care and improve management in the emergency room.